FIRST RECORD OF DACTYLONECTRIA ALCACERENSIS THAT CAUSE GRAPEVINE BLACK FOOT DISEASE IN IRAQ - SHAREEF, RIZGAR S.; HASSAN, WAZIR A. (Journal of Duhok University, 2023)
Two pathogenic isolates of the genus Dactylonectria associated with black foot disease of grape rootstocks (2-3 years old) were identified in Duhok province, Iraq. The disease incidence recorded 67% on plants that lead to weaken or plant failure when disease severity exceeded 51%. This disease is characterized by black or dark brown necrotic lesions at the bottom of rootstocks, sparse foliage and plant growth reduction. The molecular identification of CD8 and CD9 isolates, revealed that they were 100% identical to D. alcacerensis, both isolates were deposited in the national center for biotechnology information (NCBI) under accession numbers ON129803 and ON129804 respectively